Identifikasi Competitive Set The Ritz-Carlton Bali - Ni Wayan Ayu Indah Megayanti; I Nyoman Sudiksa; Ida Ayu Kalpikawati (JURNAL BISNIS HOSPITALITI, 2020)
The purpose of this study is to analyze the competitor identification by the management of The Ritz-Carlton Bali as well as hotels which are competitors to The Ritz-Carlton Bali. The data used in this study were secondary data and primary data obtained through data collection by observation, documentation study, and interviews to obtain information related to competitive set identification. The method used in this research is sequential mixed method design with two approaches, qualitative and quantitative approaches. The results of data analysis showed that among the 4 competitive set hotels identified by The Ritz-Carlton Bali management, only one hotel, Conrad Resort & Spa, that has a similar corporate identity, location, size, and product type to The Ritz-Carlton Bali. Meanwhile, based on the similarity of corporate identity, location, size, product type, room rate, ADR and RevPar, the hotels which are the competitive set of The Ritz-Carlton Bali are Intercontinental Bali Resort, Conrad Bali Resort, Ayana Resort & Spa Bali Hotel, Hilton. Bali Resort, and The Apurva Kempinski Bali.